2001
DOI: 10.1016/s0014-5793(01)02084-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gastrin receptor gene expression in proliferating cells in the neck zone of gastric fundic glands using laser capture microdissection

Abstract: Gastrin stimulates proliferation of progenitor cells in the neck zone of gastric fundic mucosa. However, whether it directly enhances this proliferation through its receptors remains unclear. We investigated the expression of gastrin receptors in neck zone proliferating cells in rat gastric fundic glands using a reverse transcription polymerase chain reaction (RT-PCR) coupled with laser capture microdissection and in situ RT-PCR. Gastrin receptor expression was identified in c-fos-expressing cells located in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Fresh frozen colon tissues were cut into 5-m-thick sections using a cryostat, then mounted on noncoated glass slides, fixed immediately with 70% ethanol for 30 s, and washed with diethylpyrocarbonate (DEPC)-treated water for 30 s. Next, the sections were stained rapidly with hematoxylin for 30 s, dehydrated by passage through an ethanol gradient, counterstained with eosin Y for 1 min, dehydrated again with an ethanol gradient, cleared with xylene, and air-dried. The sections were laser microdissected using the laser-capture microdissection (LCM) system LM200 (Olympus, Tokyo, Japan), as reported previously (18). In brief, tissue sections on slides were placed on the stage of a microscope, and an area of tissue was selected and covered with LCM transfer film.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh frozen colon tissues were cut into 5-m-thick sections using a cryostat, then mounted on noncoated glass slides, fixed immediately with 70% ethanol for 30 s, and washed with diethylpyrocarbonate (DEPC)-treated water for 30 s. Next, the sections were stained rapidly with hematoxylin for 30 s, dehydrated by passage through an ethanol gradient, counterstained with eosin Y for 1 min, dehydrated again with an ethanol gradient, cleared with xylene, and air-dried. The sections were laser microdissected using the laser-capture microdissection (LCM) system LM200 (Olympus, Tokyo, Japan), as reported previously (18). In brief, tissue sections on slides were placed on the stage of a microscope, and an area of tissue was selected and covered with LCM transfer film.…”
Section: Methodsmentioning
confidence: 99%
“…Samples captured by 5,000 shots on each transfer film cap were immersed in RNA extraction solution. To exclude the possibility that contaminating cells within the colonic epithelial preparation may be responsible for the detection of RPTP-␤ expression, we performed RT-PCR to detect the cytokeratin-20 (an epithelial maker) and CD45 (pan-leukocyte maker) mRNA simultaneously in LCM samples, as reported previously (13,18,36).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Hirayama et al (1999) have shown that poorly differentiated adenocarcinomas as well as carcinoid tumors develop during H. pylori-induced gastritis with hypergastrinemia. Recent studies have shown that gastrin receptors are present on gastric mucosal progenitor cells, suggesting that gastrin has direct trophic actions on gastric mucosal cells (Kazumori et al, 2001;Nakajima et al, 2002). On the other hand, several investigators have reported that gastrin promotes gastric mucosal cell proliferation indirectly by stimulating the production of growth factors such as TGF-␣, heparinbinding epidermal growth factor-like growth factor, and Reg (Fukui et al, 1998;Miyazaki et al, 1999;Wang et al, 2000).…”
Section: Fukui Et Almentioning
confidence: 99%
“…Rat toxicity studies conducted during the development of the world's first clinical application of PPI also reDepartment of Internal Medicine, Saga Medical School, Japan and Departments of Comprehensive Medicine and Psychosomatic Medicine, Tohoku University Hospital, Japan vealed that enterochromaffin-like (ECL) cell carcinoids develop in the stomach as a result of long-term PPI administration (6). Long-standing hypergastremia resulting from the potent gastric acid-suppressing action of PPI is believed to be a major factor in this, because gastrin might have a trophic effect on gastric mucosal cells (7). Considering those concerns, many clinical studies involving the long-term administration of PPI for several years have been conducted in Europe and the US, confirming the absence of problems in terms of tolerability (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%